A integração do smartphone em sequência de ensino de estatística para o desenvolvimento do conhecimento tecnológico, pedagógico e do conteúdo - Melo, Elvis Medeiros de (2019)
The technological advances that have taken place over the last years have been putting the human being in front of a multitude of information that is propagated, in real time, by the most diverse media, such as smartphones. The way information is presented by the media (newspapers, magazines, news, among others) does not always favor its understanding by the individual, the inability to read this information or the incorrect disclosure of statistical representation. For a citizen to be reflective and independent, he needs to be clear about the events around him. Therefore, it is important that you can treat the information presented to you critically to make decisions and to exercise full citizenship. From this reality, the question arises: How are the Technological, Pedagogical and Content (TPACK) knowledge integrated in Statistics classes with the use of smartphones? Thus, the object of this study was the analysis of how TPACK knowledge is integrated with the use of smartphones in teaching statistics. Thus, this objective analyzes the integration of TPACK knowledge for the use of smartphones in Statistics classes. The theoretical framework about the mobile digital technology inserted in education is presented, as well as the integration of Technological, Pedagogical and Content knowledge (TPACK) in the teaching of Statistics with the use of smartphones. In the technological dimension, the importance in the BYOD (Bring your own device) model is analyzed; in pedagogical, the PPDAC model (Problem, Plan, Data, Analysis, Conclusion) in the preparation of contextualized teaching sequences, as well as the didactic strategies taken by the teacher; and in the content dimension the development of the skills present in the National Common Curriculum Base (BNCC) and Prova Brasil regarding scientific research. We observed the shy use of the smartphone in the scenario of research raised through a Systematic Literature Review and that, although there has been an increase in studies over the years, none has made use of smartphone apps for the Treatment of Information. We adopt collaborative research procedures in accordance with the D-ESTAT (Professional Development of Teachers Teaching Statistics) project to which this research is linked. The subjects were Mathematics teachers from the final years of elementary school of a school in Natal / RN. In the methodological procedures, the PPDAC model was used in the teaching of Statistics during the formative process, through the elaboration of a teaching sequence using smartphones, as well as studies of statistical concepts and technologies. The co-situation stage, according to the collaborative research procedures, has been happening since May 2018 with the formation of D-ESTAT, when the project started in school. The cooperation took place concurrently with the formative meetings. Experience reports, productions at each stage of the investigative cycle were collected and reported through field diary analysis, audio, video and photo recordings. Already the co-production occurred at the time of planning and application of the teaching sequence. As a result, the teacher recognized the use of the smartphone with the amplification of his knowledge TPACK during the training process, as he used tools proposed at the time of training on the pedagogical use of the smartphone, such as the Plickers and Kahoot! apps, QR-Code and Google Forms, as well as in the elaboration of a teaching sequence and its application, involving the theme of violence as problematized of the PPDAC, according to the reality of the school. The collaborative training made the teachers reflect on their practices and prospect ways to integrate smartphones in the teaching of Statistics.